Seed Micromorphology, In Vitro Germination, and Early-Stage Seedling Morphological Traits of Cattleya purpurata (Lindl. & Paxton) Van den Berg - Miriam Bazzicalupo (MDPI AG, 2021)
In the context of a symbiotic plant-fungus interaction study concerning Cattleya purpurata, we focused on some aspects of seed morphology and biology, and the early stages of seedling development. Seed morphology was characterized using light and scanning electron microscopy. In vitro seed germination capability was evaluated, comparing symbiotic and asymbiotic methods. The morphology of the seeds was overall comparable to that of other congeneric species, showing classical adaptations related to the aerodynamic properties and to the wettability of seeds, but calcium oxalate druses were identified inside the suspensor cells. Asymbiotic seed germination was successful in all tested media (17.1–46.5%) but was higher on 1/2 Murashige & Skoog. During symbiotic interaction with the fungal strain MUT4178 (Tulasnella calospora), germination rate was significantly lower than that obtained with the best three asymbiotic media, suggesting a low fungal compatibility. Seedling morphology was in line with other taxa from the same genus, showing typical characteristics of epiphytic species. Our observations, in particular, highlighted the presence of stomata with C-shaped guard cells in the leaves, rarely found in Cattleyas (where usually they are reniform), and confirm the presence of tilosomes in the roots. Idioblasts containing raphides were observed in both roots and leaves.